Kinetics of endothelin-1 and effect selective ETA antagonism on ETB activation: a mathematical modeling analysis - Hallow, K. Melissa; Greasley, Peter J.; Heerspink, Hiddo J. L.; Yu, Hongtao (Frontiers in Pharmacology, 2024)
Endothelin-1 (ET-1) regulates renal and vascular function, but the clinical utility of selective ETA receptor antagonists has been limited due to associated fluid retention. The mechanisms underlying fluid retention remain poorly understood, but could be a consequence of changes in ET-1 binding to the unantagonized ETB receptor, either through increased ET-1 or non-selective ETB. A mathematical model of ET-1 kinetics was developed to quantify effects of ETA antagonist exposure and selectivity on concentrations of ET-1 and its complexes with ETA and ETB receptors. The model describes ET- production, tissue and plasma distribution, ETA and ETB receptor binding, and receptor-mediated clearance, and was calibrated and validated with human ET-1 infusion studies. The model confirmed the significant role of ETB in ET-1 clearance. By varying both drug ETA selectivity (Kib / Kia) and concentration over a wide range, simulations predicted that while selective ETA antagonist (selectivity > 1) always decreased [ET1-ETA], the change in [ET1-ETB] was more complex. It increased up to 45% as drug concentrations approached and exceeded Kia, but the increase was diminished as drug concentration increased further, and fell below baseline at high concentrations.The drug concentration required to cause a decrease in [ET1-ETB] was lower as ETA selectivity decreased. This study provides quantitative insights into the complex interplay between ET-1, its receptors, and antagonist selectivity.